Installation of Environmental Technology for Water Retention at the University Farm of UFRPE/UAG - Vasconcelos, José Victor Ávila Correia de (Journal of Hyperspectral Remote Sensing, 2017)
Due to the greatest drought problems in the Northeast region of Brazil, especially in the Semi-arid region of the State of Pernambuco, and the lack of sustainable water and soil conservation technologies, this work aims to apply the BAPUCOSA Methodology (Barrier with Used Tires for Containment of Soil and Water), at the University Farm of UFRPE (Federal Rural University of Pernambuco – Brazil), developed by Baracuhy (2007), which promotes the partial obstruction of the surface water flow and of the soils carried in temporary channels, promoting a greater storage of water. In addition to this, the water storage capacity of this dam was calculated, disregarding soil infiltration and recommended more in-depth studies on this subject.